Study on Dynamic Problem of Speed-increasing EMUs on Lanzhou-Xinjiang Passenger Dedicated Line - Guodong LI; Litong CUI; Wenhua WANG; Xiaofeng LI (机车电传动)
The Lanzhou-Xinjiang passenger dedicated Line is located in the northwest region of China with the natural environment of high temperature, severe cold and windy sand, which puts forward higher requirements for the safe and reliable operation of high-speed EMUs. When the running speed was 200 km/h, the EMUs operated in good condition. After the speed was increased to 250 km/h, the dynamic indicators such as the frame lateral acceleration and lateral ride index would significantly be increased, and be close to the limit values in some conditions. From the perspective of wheel wear, actual wheel-rail matching relationship and application environment, simulation analysis and vibration test were used to find the cause of the deterioration of vehicle dynamic performance. the lateral stability was improved by improving the rail profile, optimizing suspension parameters, and adjusting operation routes, the vehicle dynamic problems were solved well after the EMUs speed increase.